CURRENT STATE OF INNOVATIVE DEVELOPMENT BANKING SYSTEM OF UKRAINE (Socio-economic relations in the digital society, 2019)
In the article the analysis of modern state and tendencies of development of innovations in the banking system of Ukraine. Th e features of the innovation process in banks, as well as identifi ed leaders in innovation in the banking sector. The main purpose of this article is the study of innovation in the banking system of Ukraine, as well as analysis of trends introduction of innovative products in the banking market. The article is actual, because of in the banks of Ukraine, management of innovations, consists only in the decision of active jobs, and his quality does not answer a world level and national necessities of development of the banking system. Therefore, actual is research of innovative development status in the banking system of Ukraine.
Keywords: innovation; banking innovation; online banking; mobile banking; banking services; banking